A special admixture for 3D printing concrete and preparation method thereof
By using 3D-printed concrete-specific admixtures containing water-reducing frameworks, modified thixotropic particles and slow-soluble layers, the existing admixtures are solved in 3D printing, and the high flowability and rapid coagulation performance of concrete are achieved.
Patent Information
- Application Number
- CN202211695104.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-12-28
AI Technical Summary
Existing 3D printed concrete admixtures cannot effectively meet the needs of 3D printing, resulting in insufficient concrete fluidity or low condensation rate, which in turn affects the integrity of the product.
A 3D printed concrete special admixture is used that includes a water-reducing skeleton, a modified thixotropic particles formed in the water-reducing skeleton, and a slow-soluble layer coated on the surface of the water-reducing skeleton. The water-reducing skeleton is made of modified polycarboxylic acid and skeleton material. The modified thixotropic particles are typed into the water-reducing skeleton through coupling agent, and the slow-soluble layer is composed of gypsum and water-soluble film.
The high flowability of concrete in the early stage and the rapid coagulation performance in the later stage are achieved, and the problem of insufficient fluidity or poor rapid coagulation effect in 3D printing is solved.
Smart Images

Figure BDA0004023101960000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete 3D printing, and in particular to a special admixture for 3D printing concrete and a preparation method thereof. Background Art
[0002] Concrete is an engineering composite material that is made of aggregates bonded together by cementitious materials. It is one of the most important and commonly used civil engineering materials. With the rapid development of industries such as construction, machinery, and shipbuilding, the use and demand of concrete has greatly increased, and with it come problems such as low efficiency in concrete construction and high workload in traditional construction methods.
[0003] 3D printing, also known as additive manufacturing, is a manufacturing method based on a three-dimensional model, which uses a layer-by-layer stacking method that is completely opposite to traditional subtractive manufacturing technology to directly manufacture a three-dimensional physical model that is completely consistent with the corresponding digital model. At present, concrete materials have been introduced into 3D printing technology. The use of 3D printing concrete technology to build houses has the advantages of mold-free construction, labor and material saving, and high construction efficiency.
[0004] Based on the differences between 3D printing technology and traditional construction methods, concrete using 3D printing technology needs to have good rheological properties, pumpability, printability (extrusion molding and layered stacking), mechanical properties and durability. Traditional concrete materials cannot meet the above 3D printing conditions, so admixtures are usually added to the concrete raw materials to improve the various properties of the concrete materials. However, adding conventional concrete admixtures cannot make concrete meet the performance conditions required for 3D printing, and it is easy to have problems such as molding failure, insufficient strength or poor durability.
[0005] Therefore, we urgently need a special admixture for 3D printing concrete to better realize 3D printing concrete. Summary of the invention
[0006] The technical problems to be solved by the present invention are:
[0007] At present, in 3D printing concrete technology, the addition of additives to 3D printing concrete cannot make the concrete slurry meet the needs and standards of 3D printing well. Specifically, during the 3D printing process, the fluidity of the concrete is insufficient, or the concrete setting rate is low after printing, which leads to problems such as poor product integrity. In other words, it is difficult to simultaneously achieve the use effect of high fluidity of the concrete in the early stage and good rapid setting effect in the later stage.
[0008] The technical solution adopted by the present invention is:
[0009] The present invention provides a special admixture for 3D printing concrete, comprising a water-reducing skeleton, modified thixotropic particles typed into the water-reducing skeleton, and a slow-dissolving layer coated on the surface of the water-reducing skeleton; in terms of mass ratio, the amount ratio of the water-reducing skeleton to the modified thixotropic particles is 1:0.8-1.25; in terms of mass fraction, the slow-dissolving layer accounts for 16-27% of the total mass of the admixture.
[0010] Preferably, the water-reducing skeleton comprises a modified polycarboxylic acid, the side chains of the modified polycarboxylic acid are connected with unsaturated groups, and the main chain of the modified polycarboxylic acid is connected with rigid groups.
[0011] Preferably, the water-reducing skeleton further comprises a skeleton material, and the skeleton material comprises one or more of nano-SiO2 and carbon nanotubes.
[0012] Preferably, the modified thixotropic particles include polyaluminium sulfate and diethylamino alcohol.
[0013] Preferably, the preparation method of the modified thixotropic particles comprises the following steps: dissolving polyaluminium sulfate and diethylamine alcohol in carboxylic acid, mixing, and distilling and drying; taking a molding agent, and preparing the modified thixotropic particles by spray granulation.
[0014] Preferably, the slow-dissolving layer comprises gypsum and a water-soluble film, the gypsum is coated on the surface of the water-reducing skeleton, and the water-soluble film is coated on the surface of the gypsum.
[0015] Preferably, the water-soluble film comprises one or more of a polyvinyl alcohol water-soluble film, a guar gum water-soluble film or a gelatin water-soluble film.
[0016] Preferably, the thickness of the water-soluble film is ≤25 μm.
[0017] The present invention also provides a method for preparing the above-mentioned special admixture for 3D printing concrete, comprising the following steps:
[0018] S1: taking a water-reducing skeleton and modified thixotropic particles according to the amount, mixing, adding an oxygen-containing silane coupling agent and a catalyst, placing in a silicone oil bath and heating to 80-100°C, reacting for 5-8h, inserting the modified thixotropic particles into the water-reducing skeleton by hydrosilylation, and then drying and granulating to obtain intermediate particles I;
[0019] S2 adds gypsum to the intermediate particles I, rotates and stirs to obtain intermediate particles II; takes the water-soluble film solution, applies it on the surface of the intermediate particles II, and shade-dries, repeats for several times to obtain admixture particles.
[0020] Preferably, the particle size of the intermediate particles I is 85-135 μm, and the particle size of the intermediate particles II is 80-150 μm.
[0021] The beneficial effects of the present invention are as follows:
[0022] (1) The admixture in the present invention adopts a multi-layered particle structure, the outer layer of the particle is mainly a substance that promotes fluidity, and the inner part of the particle is mainly a substance that improves the rapid setting effect, which can simultaneously achieve the effects of good early fluidity and good later rapid setting performance.
[0023] (2) The water-reducing skeleton is embedded and mixed by ultrasonic dispersion of modified polycarboxylic acid and skeleton material. The main chain of the modified polycarboxylic acid is connected with rigid groups, which has obvious steric hindrance effect and can form a water-reducing skeleton with stable spatial structure. The modified polycarboxylic acid in the water-reducing skeleton and the modified thixotropic particles are embedded and connected by a coupling agent: the silicon-hydrogen bond in the coupling agent is added to the unsaturated bond connected to the side chain of the modified polycarboxylic acid, and the modified thixotropic particles are stably typed into the water-reducing skeleton through the coupling agent, which plays a good role in accelerating the setting of concrete after it is extruded from the 3D printing equipment.
[0024] (3) In the modified thixotropic particles, diethylamino alcohol reacts with carboxylic acid to generate amide groups, and the particles are keyed into the water-reducing skeleton through a coupling agent, thereby maintaining the stability of the spatial structure of the water-reducing skeleton and preventing the modified thixotropic particles from denaturing and failing during storage, thereby improving their stability and having a good quick-setting effect.
[0025] (4) Gypsum and a water-soluble film wrapped on the surface of the gypsum. The water-soluble film can release the substances in the film during the hydration process. Before use, the gypsum blocks the contact reaction between the inner layer material and the external environment to ensure the stability of the admixture before use. Gypsum is used to block the contact between the water-soluble film and the inner layer material to avoid the water-soluble film from being damaged. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The present invention provides a special admixture for 3D printing concrete, comprising a water-reducing skeleton, modified thixotropic particles typed into the water-reducing skeleton, and a slow-dissolving layer coated on the surface of the water-reducing skeleton; wherein, by weight, the water-reducing skeleton accounts for about 35-48 parts, the modified thixotropic particles account for about 30-50 parts, and the slow-dissolving layer accounts for about 16-27 parts.
[0028] In the present invention, the water-reducing skeleton is prepared from modified polycarboxylic acid and skeleton material: the modified polycarboxylic acid and the skeleton material are mixed and dissolved in a solvent, and ultrasonic dispersion is performed to obtain the water-reducing skeleton. The modified polycarboxylic acid is a polycarboxylic acid having a carbon-carbon unsaturated group grafted on the side chain and a rigid group on the main chain, and the carbon-carbon unsaturated group is vinyl, propylene, etc.; the rigid group is a benzene ring, etc., which can increase the steric hindrance effect of the water-reducing skeleton and keep its structure stable; the skeleton material is a material whose molecular structure forms a spatial framework structure such as nano-SiO2 or carbon nanotubes, so that the water-reducing skeleton maintains a loose, porous and stable structural form.
[0029] In the present invention, in the water-reducing skeleton, the side chains of the modified polycarboxylic acid contain carbon-carbon unsaturated bonds. The water-reducing skeleton is mixed with modified thixotropic particles, and after introducing an oxygen-containing silane coupling agent and a catalyst, it is placed in a silicone oil bath for heating reaction to form silicon-hydrogen bonded particles supported by the water-reducing skeleton and wrapped with the modified thixotropic particles, which play a quick-setting effect in the later stage of printing.
[0030] In the present invention, the outer layer is wrapped with gypsum, and then wrapped with a molten water-soluble film, which is cooled to form a film wrapped on the outermost layer. The water-soluble film can release the substance in the film during the hydration process, and before use, the gypsum blocks the contact reaction between the inner layer material and the external environment, thereby ensuring the stability of the admixture before use; at the same time, the gypsum also plays a role in blocking the contact between the water-soluble film and the inner layer material, thereby ensuring the stability of the admixture before use.
[0031] In the present invention, the particle size of the water-reducing skeleton is about 60-110 μm; after the modified thixotropic particles are added, the particle size increases to about 85-135 μm, and the modified thixotropic particles are bonded to the frame gap and frame surface of the water-reducing skeleton; after being coated with gypsum and water-soluble film, the admixture particles are obtained, and the particle size is about 100-150 μm. When the admixture is put into the concrete for 3D printing, the outer layer of the admixture particles first contacts with cement, etc., and the cement is hydrated. After the concrete is extruded from the extrusion port of the 3D printing device, the surface material of the admixture is fully combined with the concrete. At this time, the modified thixotropic particles and the water-reducing skeleton are exposed to the concrete, and the rapid setting effect is exerted, that is, the effect of high fluidity in the early stage and strong rapid setting effect in the later stage is achieved.
[0032] Example 1
[0033] According to the mass percentage, 18.5 parts of modified polycarboxylic acid, 21 parts of nano-SiO2, 12 parts of polyaluminum sulfate, 10.5 parts of diethylamino alcohol, 20 parts of gypsum and 10.75 parts of polyvinyl alcohol water-soluble film were weighed; wherein, the modified polycarboxylic acid is a polycarboxylic acid with vinyl grafted on the side chains and benzene ring on the main chain, and the molecular weight of the modified polycarboxylic acid is about 22000.
[0034] Prepare the special admixture for 3D printing concrete as follows:
[0035] (1) firstly take modified polycarboxylic acid and nano-SiO2, mix them and dissolve them in a 75% ethanol solution, heat them to about 80°C, and disperse them ultrasonically for 25 minutes to prepare a water-reducing skeleton embedded with modified polycarboxylic acid and nano-SiO2, the particle size of which is about 110 μm. According to the actual preparation situation, if the particle size of the obtained water-reducing skeleton is large, it is crushed to the required particle size; separately take polyaluminum sulfate and diethylamino alcohol, dissolve them in oxalic acid solution, stir them to react until they are completely dissolved, and then distill and dry them to remove excess water; take a sufficient amount of 70% ethanol solution as a molding agent, and prepare modified thixotropic particles by spray granulation;
[0036] (2) mixing the water-reducing skeleton with the modified thixotropic particles, and adding an oxygen-containing silane coupling agent KH-560 and a catalyst, wherein the oxygen-containing silane coupling agent is KH-560, and the catalyst is a carboxylic acid calcium salt cyclized polyether-N-heterocyclic carbene platinum complex, placing the mixture in a silicone oil bath, stirring and heating to about 85° C., reacting for about 6.5 hours, and after drying, spraying and granulating the mixture using a 70% by volume ethanol solution;
[0037] Then, the gypsum slurry is added to the prepared particles, and the particles are rotated and stirred at a speed of 850 r / min. After natural air drying, the sticky large particles are crushed with a crusher to obtain homogeneous small particles; a polyvinyl alcohol water-soluble film solution with a concentration of 1 wt% is taken, coated on the surface of the small particles, and dried in the shade; the coating and shade-drying operations are repeated three times to obtain an additive whose surface is uniformly coated with a polyvinyl alcohol water-soluble film.
[0038] Example 2
[0039] 20 parts of modified polycarboxylic acid, 18 parts of carbon nanotubes, 12 parts of polyaluminum sulfate, 10.5 parts of diethylamino alcohol, 17 parts of gypsum and 8 parts of guar gum water-soluble film were weighed by mass; wherein the modified polycarboxylic acid is a polycarboxylic acid having vinyl groups in the side chains and benzene rings in the main chains, and the molecular weight of the modified polycarboxylic acid is about 26,000.
[0040] Prepare the special admixture for 3D printing concrete as follows:
[0041] (1) firstly take modified polycarboxylic acid and carbon nanotubes, mix them and dissolve them in a 75% ethanol solution, heat them to about 80° C., and ultrasonically disperse them for 25 minutes to prepare a water-reducing skeleton with a particle size of about 110 μm; separately take polyaluminum sulfate and diethylamino alcohol, dissolve them in an oxalic acid solution, stir and react until they are completely dissolved, and then distill and dry them to remove excess water; take a sufficient amount of 70% ethanol solution as a molding agent, and prepare modified thixotropic particles by spray granulation;
[0042] (2) mixing the water-reducing skeleton with the modified thixotropic particles, adding KH-560 oxygen-containing silane coupling agent and carboxylic acid calcium salt cyclized polyether-N-heterocyclic carbene platinum complex catalyst, placing in a silicone oil bath, stirring and heating to about 85° C., reacting for about 6.5 hours, drying, and spraying granulation using a 70% by volume ethanol solution;
[0043] Then, the gypsum slurry is added to the prepared particles, and the particles are rotated and stirred at a speed of 850 r / min. After natural air drying, the sticky large particles are crushed with a crusher to obtain homogeneous small particles; 1wt% guar gum water-soluble film solution is taken, coated on the surface of the small particles, and dried in the shade; the coating and shade drying operations are repeated three times to obtain an admixture whose surface is uniformly coated with the guar gum water-soluble film.
[0044] Example 3
[0045] 19 parts of modified polycarboxylic acid, 20 parts of nano-SiO2, 10 parts of polyaluminum sulfate, 10.5 parts of diethylamino alcohol, 20 parts of gypsum and 12 parts of guar gum water-soluble film were weighed by mass; wherein the modified polycarboxylic acid is a polycarboxylic acid with vinyl grafted on the side chains and benzene ring on the main chain, and the molecular weight of the modified polycarboxylic acid is about 30,000.
[0046] Prepare the special admixture for 3D printing concrete as follows:
[0047] (1) firstly take modified polycarboxylic acid and nano-SiO2, mix them and dissolve them in a 75% ethanol solution, heat them to about 80°C, and disperse them ultrasonically for 25 minutes to prepare a water-reducing skeleton with a particle size of about 110 μm; separately take polyaluminum sulfate and diethylamino alcohol, dissolve them in an oxalic acid solution, stir them to react until they are completely dissolved, and then distill and dry them to remove excess water; take a sufficient amount of 70% ethanol solution as a molding agent, and prepare modified thixotropic particles by spray granulation;
[0048] (2) mixing the water-reducing skeleton with the modified thixotropic particles, adding KH-560 oxygen-containing silane coupling agent and carboxylic acid calcium salt cyclized polyether-N-heterocyclic carbene platinum complex catalyst, placing in a silicone oil bath, stirring and heating to about 85° C., reacting for about 6.5 hours, drying, and spraying granulation using a 70% by volume ethanol solution;
[0049] Then, the gypsum slurry is added to the prepared particles, and the particles are rotated and stirred at a speed of 850 r / min. After natural air drying, the sticky large particles are crushed with a crusher to obtain homogeneous small particles; 1wt% guar gum water-soluble film solution is taken, coated on the surface of the small particles, and dried in the shade; the coating and shade drying operations are repeated three times to obtain an admixture whose surface is uniformly coated with the guar gum water-soluble film.
[0050] Example 4
[0051] 18.5 parts of modified polycarboxylic acid, 21 parts of carbon nanotubes, 12 parts of polyaluminum sulfate, 10.5 parts of diethylamino alcohol, 20 parts of gypsum and 12 parts of gelatin water-soluble film were weighed by mass; wherein the modified polycarboxylic acid is a polycarboxylic acid having a propenyl group as a branch chain and a benzene ring as a main chain, and the molecular weight of the modified polycarboxylic acid is about 24,000.
[0052] Prepare the special admixture for 3D printing concrete as follows:
[0053] (1) firstly take modified polycarboxylic acid and carbon nanotubes, mix them and dissolve them in a 75% ethanol solution, heat them to about 80° C., and ultrasonically disperse them for 25 minutes to prepare a water-reducing skeleton with a particle size of about 110 μm; separately take polyaluminum sulfate and diethylamino alcohol, dissolve them in an oxalic acid solution, stir and react until they are completely dissolved, and then distill and dry them to remove excess water; take a sufficient amount of 70% ethanol solution as a molding agent, and prepare modified thixotropic particles by spray granulation;
[0054] (2) mixing the water-reducing skeleton with the modified thixotropic particles, adding KH-560 oxygen-containing silane coupling agent and carboxylic acid calcium salt cyclized polyether-N-heterocyclic carbene platinum complex catalyst, placing in a silicone oil bath, stirring and heating to about 90° C., reacting for about 6.5 hours, drying, and spraying granulation using a 70% by volume ethanol solution;
[0055] Then, add the gypsum slurry to the prepared particles, rotate and stir at a speed of 850r / min, and after natural air drying, use a crusher to break up the sticky large particles to obtain homogeneous small particles; take 1wt% gelatin water-soluble film solution, apply it on the surface of the small particles, and dry in the shade; repeat the coating and shade-drying operations three times to obtain an additive with a surface uniformly coated with a gelatin water-soluble film.
[0056] Example 5
[0057] According to the mass percentage, 22 parts of modified polycarboxylic acid, 20 parts of nano-SiO2, 10 parts of polyaluminum sulfate, 9 parts of diethylamino alcohol, 18 parts of gypsum and 10.5 parts of gelatin water-soluble film were weighed; wherein, the modified polycarboxylic acid is a polycarboxylic acid with acryl grafted on the side chain and a benzene ring on the main chain, and the molecular weight of the modified polycarboxylic acid is about 28000.
[0058] Prepare the special admixture for 3D printing concrete as follows:
[0059] (1) firstly take modified polycarboxylic acid and nano-SiO2, mix them and dissolve them in 75% ethanol solution, heat them to about 80°C, and ultrasonically disperse them for 25 minutes to prepare a water-reducing skeleton with a particle size of about 110 μm; separately take polyaluminum sulfate and diethylamino alcohol, dissolve them in oxalic acid solution, stir and react until they are completely dissolved, and then distill and dry them to remove excess water; take a sufficient amount of 70% ethanol solution as a molding agent, and prepare modified thixotropic particles by spray granulation;
[0060] (2) mixing the water-reducing skeleton with the modified thixotropic particles, adding KH-560 oxygen-containing silane coupling agent and carboxylic acid calcium salt cyclized polyether-N-heterocyclic carbene platinum complex catalyst, placing in a silicone oil bath, stirring and heating to about 95° C., reacting for about 6 hours, drying, and spraying granulation using 70% ethanol solution;
[0061] Then, add the gypsum slurry to the prepared particles, rotate and stir at a speed of 850r / min, and after natural air drying, use a crusher to break up the sticky large particles to obtain homogeneous small particles; take 1wt% gelatin water-soluble film solution, apply it on the surface of the small particles, and dry in the shade; repeat the coating and shade-drying operations three times to obtain an additive with a surface uniformly coated with a gelatin water-soluble film.
[0062] <Test example>
[0063] Samples: the admixtures in Examples 1-5, polycarboxylate water-reducing agent, alumina clinker accelerating agent, and the composite of polycarboxylate water-reducing agent and alumina clinker accelerating agent are respectively referred to as Test Examples 1-8.
[0064] Test: The above samples were used as test examples 1-7, and were added to silicate cement and sulphoaluminate cement for 3D printing. The hardening speed of the products and the integrity of the surface morphology of the products during the printing process were summarized. The results are recorded as follows:
[0065] Table 1 3D printing product hardening speed and product surface morphology integrity
[0066]
[0067] It can be seen from the above table:
[0068] (1) When the admixtures in Examples 1-5 are used in 3D printed concrete, the hardening and molding time of the concrete slurry after being extruded from the discharge nozzle of the 3D printing equipment is significantly shorter than the time required for hardening and molding of the 3D printed concrete using conventional concrete admixtures in Test Examples 6-8, which means that the admixture of the present invention has a more significant quick-setting effect during the application process.
[0069] (2) The integrity of the product surface morphology refers to the surface morphology integrity of the product obtained by 3D printing concrete, which is expressed based on the area occupied by obvious pits or notches on its surface. This characterization can indirectly reflect the fluidity of the concrete slurry during the extrusion process. By comparison, the surface morphology integrity of the products in Examples 1-5 is slightly higher than that of the products obtained in Test Examples 6-8.
[0070] (3) In combination with the admixtures in Examples 1-5 and Test Examples 6-8, the effects on the fluidity and rapid setting effect of 3D printed concrete products can be proved: compared with the existing water reducers and rapid setting agents that only have a single water reducing or rapid setting effect, the admixtures of the present invention can take into account the above two aspects of performance at the same time, and the two properties are significantly better than the performance of the composite obtained by simply mixing the existing water reducer and the rapid setting agent, solving the problem of poor rapid setting effect or poor fluidity of the traditional admixtures.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A special admixture for 3D printing concrete, characterized in that: It comprises a water-reducing skeleton, modified thixotropic particles inserted into the water-reducing skeleton, and a slow-dissolving layer coated on the surface of the water-reducing skeleton; In terms of mass ratio, the usage ratio of the water-reducing skeleton to the modified thixotropic particles is 1:0.8-1.25; in terms of mass fraction, the slow-dissolving layer accounts for 16-27% of the total mass of the admixture; The water-reducing skeleton comprises a modified polycarboxylic acid, the side chains of the modified polycarboxylic acid are connected with unsaturated groups, and the main chain of the modified polycarboxylic acid is connected with rigid groups; The modified thixotropic particles include polyaluminium sulfate and diethylamino alcohol, and the preparation method of the modified thixotropic particles includes the following steps: dissolving polyaluminium sulfate and diethylamino alcohol in carboxylic acid, mixing, distilling and drying; taking a molding agent, and preparing the modified thixotropic particles by spray granulation; The preparation method of the special admixture for 3D printing concrete comprises the following steps: S1 Take the water-reducing skeleton and modified thixotropic particles according to the amount, mix them, add the oxygen-containing silane coupling agent and the catalyst, place them in a silicone oil bath and heat them to 80-100°C, react for 5-8h, and then dry and granulate them to obtain intermediate particles I; S2: Add gypsum to the intermediate particles I, rotate and stir to obtain intermediate particles II; take the water-soluble film solution, apply it on the surface of the intermediate particles II, dry it in the shade, repeat several times, and obtain the admixture particles.
2. The special admixture for 3D printing concrete according to claim 1, characterized in that: The water-reducing skeleton also includes a skeleton material, and the skeleton material includes one or more of nano-SiO2 and carbon nanotubes.
3. The special admixture for 3D printing concrete according to claim 1, characterized in that: The slow-dissolving layer includes gypsum and a water-soluble film. The gypsum is coated on the surface of the water-reducing skeleton, and the water-soluble film is coated on the surface of the gypsum.
4. The special admixture for 3D printing concrete according to claim 3, characterized in that: The water-soluble film includes one or more of a polyvinyl alcohol water-soluble film, a guar gum water-soluble film or a gelatin water-soluble film.
5. The special admixture for 3D printing concrete according to claim 3, characterized in that: The thickness of the water-soluble film is ≤25 μm.
6. The special admixture for 3D printing concrete according to claim 1, characterized in that: The particle size of the intermediate particles I is 60-110 μm, and the particle size of the intermediate particles II is 85-135 μm.
Citation Information
Patent Citations
Setting-accelerating early strength agent suitable for cement-based 3D printing materials and preparation method thereof
CN110981254A
Coagulation-promoting early strength agent for 3D printing cement-based material
CN112592091A
Ultrafast-setting early-strength alkali-free powder accelerator applicable to wet spraying process as well as preparation method and application of ultrafast-setting early-strength alkali-free powder accelerator
CN112723786A